2003
DOI: 10.1002/cne.10612
|View full text |Cite
|
Sign up to set email alerts
|

Efferent connections of the dorsomedial thalamic nuclei of the domestic chick (Gallus domesticus)

Abstract: Small iontophoretic injections of the anterograde tracer Phaseolus vulgaris leucoagglutinin were placed in the thalamic anterior dorsomedial nucleus (DMA) of domestic chicks. The projections of the DMA covered the rostrobasal forebrain, ventral paleostriatum, nucleus accumbens, septal nuclei, Wulst, hyperstriatum ventrale, neostriatal areas, archistriatal subdivisions, dorsolateral corticoid area, numerous hypothalamic nuclei, and dorsal thalamic nuclei. The rostral DMA projects preferentially on the hypothala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 128 publications
(183 reference statements)
4
37
1
Order By: Relevance
“…Until the present study, very little was known about the connectivity of the DMA nucleus in reptiles. A recent study in birds has demonstrated projections from DMA to cortical regions [Montagnese et al, 2003]. Large HRP injections into the turtle dmCx (D1) and mCx (DM and M) were reported to result in neuronal label in the DLA and DMA thalamic nuclei [Desan, 1987], findings consistent with those reported here.…”
Section: Comparison Of Thalamocortical Projections Among Reptilessupporting
confidence: 82%
See 1 more Smart Citation
“…Until the present study, very little was known about the connectivity of the DMA nucleus in reptiles. A recent study in birds has demonstrated projections from DMA to cortical regions [Montagnese et al, 2003]. Large HRP injections into the turtle dmCx (D1) and mCx (DM and M) were reported to result in neuronal label in the DLA and DMA thalamic nuclei [Desan, 1987], findings consistent with those reported here.…”
Section: Comparison Of Thalamocortical Projections Among Reptilessupporting
confidence: 82%
“…The results revealed a topographic pattern of thalamocortical connections such that medial cortical regions connect with medial thalamic nuclei and lateral cortical regions connect with lateral thalamic nuclei. These findings, combined with the work of others [Hall and Ebner, 1970;Hall et al, 1977;Bruce and Butler, 1984a;Ulinski, 1986;Desan, 1987;Pritz, 1995;Montagnese et al, 2003], suggest that the presence of functionally segregated thalamocortical projections is a conserved feature of brain organization among amniotes. Moreover, this work describes a descending pathway linking cortical regions with the red nucleus via the nSP of the hypothalamus thereby providing indirect cortical control of the reptilian rubrospinal system.…”
Section: Introductionmentioning
confidence: 66%
“…We found that NE agonists produce a profound PPI disruption in this site; indeed, this effect was the strongest and most dose-dependent out of all the sites tested. Interestingly, the BLA and posterior mPFC both connect reciprocally with MD-thalamus; robust NE agonistinduced PPI deficits were found in these sites, but not in the DH, which does not connect to MD-thalamus (Gabbott et al, 2005;Giguere and Goldman-Rakic, 1988;Hoover and Vertes, 2007;Kuroda, 1998;Miyashita et al, 2007;Montagnese et al, 2003;Vertes et al, 2007). Moreover, the anterior mPFC, which was a 'null' site in this study, has proportionately less abundant reciprocal connections with MD-thalamus, compared with the posterior mPFC, which was a 'PPI-active' site (Gabbott et al, 2005;Hoover and Vertes, 2007).…”
Section: Discussionmentioning
confidence: 47%
“…Tract tracing studies have so far revealed inputs from a wide range of pallial structures (i.e., avian homologues of isocortex such as the arcopallium and nidopallium) [54], the subpallial thalamus [55], and neuromodulatory nuclei including the ventral tegmental area (VTA) and substantia nigra (SN) for dopaminergic afferents [56][57][58][59], and the raphe nuclei in the pons for serotonergic afferents [60].…”
Section: Afferent Connection To Mst/nacmentioning
confidence: 99%